Survey on farm practices of small-scale vegetable farmers in the Southern Philippines - Seriño, Moises Neil V.; Castillo, Glorybeth; Ruales, Jessa (Annals of Tropical Research, 2017)
This study aims to survey the farm practices of small scale vegetable farmers, evaluate gender roles in farming and assess the changes in farm income of farmers engaged in integrated crop management. The respondents of the study include randomly selected small-scale vegetable farmers trained under the farmer field school (FFS) in Bohol, Leyte and Samar. Randomly selected non-FFS farmers serve as control group. Information on farm practices between non-FFS and FFS respondents are used in determining the changes in farm outcomes. Results show that FFS and non-FFS farmers mostly planted eggplant, bitter gourd, beans, sweet pepper, pechay, squash, tomato and okra. The farm areas of surveyed respondents are mostly located around 10 kilometers away from their primary market with an approximate traveling time of half an hour. During the baseline survey, FFS farmers indicated that they are mostly unsatisfied with their current vegetable production in contrast to non-FFS farmers who expressed satisfaction with their current production. However, in the follow-up survey FFS group expressed relatively higher optimism than non-FFS group in terms of their vegetable production suggesting that the project interventions were able to encourage small scale farmers to incorporate necessary improvements in their practices. For gender roles in vegetable production, men are into labor intensive tasks while women focus mostly on record keeping and monitoring sales of vegetables. Lastly, employing the method of difference in difference shows that impact of farmer field school on integrated crop management increases vegetable farm income by around PHP4,300.00 per year per farm.